The Chronic Stages of Bovine Fasciola hepatica Are Dominated by CD4 T-Cell Exhaustion - Sachdev, Divya; Gough, Kevin C.; Flynn, Robin J. (Frontiers in Immunology, 2017)
Fasciola hepatica infection of ruminants leads to non-resolving chronic infection, as patency develops there is switching to a TGF-β and IL-10 led response. Here we explore the responses of CD4 T-cells within the major draining lymph nodes. We found minimal expression of Foxp3 within CD4 cells but elevated levels within the γδ (WC1+) population. There is a strong T-cell intrinsic exhaustion phenotype within the hepatic lymph node (HLN) characterised by a lack of antigen-specific proliferation and cytokine secretion. CD4 T-cells recovered from the HLN had high levels of PD-1 expression and low levels of IL-2 secretion. Exogenous IL-2 partially rescued this defect; when combined with neutralisation of IL-10 and TGF-β, full restoration of proliferation and cytokine production was achieved. Moreover, there is a clear uncoupling of the mechanisms that facilitate this regulation with parasite specific proliferation and cytokine secretion being governed by independent means. These data would suggest that there is a CD4 T-cell intrinsic regulation in place early in chronic infection, potentially leading to failure in resistance to reinfection.